2017
DOI: 10.9790/9622-0706036684
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis to Forecast Air Quality Indices in Thiruvananthapuram District, Kerala, India

Abstract: Highlights Air Quality Index (AQI) of Thiruvananthapuram city has been calculated  AQI forecasting using ARIMA and SARIMA model were introduced  Error between actual and predicted AQI has been reduced using optimization technique ABSTRACTDeterioration of air quality is an important issue faced by many cities in India. The increase in the number of vehicles, unrestrained burning of plastics, unacceptable construction and demolition activities and industrial activities are the main reasons for this deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For instance, Xiang-Li et al (2017) analysed air quality in Beijing from 2014 to 2016 using a novel long shortterm memory neural network extended (LSTME) model, and showed that this specification is superior to others to model time series with long-term dependence and to capture spatio-temporal correlations and improve predictions. Naveen et al (2017) estimated ARIMA and SARIMA models to study air quality in India, and found that the former outperforms the latter. Zhongfei et al (2016) analysed pollution in four Chinese cities from 2013 to 2015 using fractional integration methods and found a high degree of persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Xiang-Li et al (2017) analysed air quality in Beijing from 2014 to 2016 using a novel long shortterm memory neural network extended (LSTME) model, and showed that this specification is superior to others to model time series with long-term dependence and to capture spatio-temporal correlations and improve predictions. Naveen et al (2017) estimated ARIMA and SARIMA models to study air quality in India, and found that the former outperforms the latter. Zhongfei et al (2016) analysed pollution in four Chinese cities from 2013 to 2015 using fractional integration methods and found a high degree of persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accurate air quality predictions are useful, for example, individual activity arrangements and government pollution restrictions can benefit from air quality time series in New Delhi. Naveen et al [13] then adopted the seasonal autoregressive integrated moving average (SARIMA), which can capture the seasonal feature of time series, to predict the air quality in Kerala. However, due to the complexity and uncertainty of air quality prediction tasks, it is difficult for the statistical methods to perform well for longterm predictions.…”
Section: Introductionmentioning
confidence: 99%
“…In India, Naveen and Anu [22] analyzed and forecasted the varying trend of outdoor air quality using the dataset recorded at different monitoring air quality stations in the district of Thiruvananthapuram, Kerala, India. The analysis was conducted using the Seasonal Autoregressive Integrated Moving Average (SARIMA) and ARIMA models, and ARIMA model was observed to have performed better in giving more accurate forecast values.…”
Section: Introductionmentioning
confidence: 99%